KAJIAN DAMPAK EFEK SAMPING PENGGUNAAN OBAT OFF LABEL PADA PASIEN SISTEMIK LUPUS ERITEMATOSUS (SLE) TERHADAP BIAYA KESEHATAN - Iwan Yuwindry; Yusri Yusri; Hansel Hens Tangkas (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
The main problem in conducting lupus treatment is that most drugs for the therapy provided have not been authorized so that they are still included in the class of off-label drugs for the treatment of lupus. The purpose of this study was only to see the impact of side effects of off-label drugs on health costs. This study was conducted using a cross-sectional method by means of a survey using the Naranjo Algorithm instrument (PESO Book) to determine the level of incidence of side effects that exist in LSE therapy using off-label drugs and calculate the health costs of lupus patients. The results showed that the most respondents were in adulthood (19 respondents  47.5%), then the most respondents were female (37 respondents or 92.5%). Data on the incidence of side effects obtained the most respondents in the Probable category (most likely to occur ROM) of 14 respondents or 35%. In addition, data on health costs incurred by more respondents experienced an increase, namely 23 respondents or 57.5%. The research data shows the calculated r value is 0.3044 and the Sig (2-tailed) value is 0.000 with a confidence level (CI) of 0.05. The results of the analysis clearly show that there is a significant relationship between the side effects of using off-label drugs on the health costs of lupus patients, where if the value of side effects experienced by respondents is high, the value of respondents' health costs is also high.